Expanding the desired form, we have
![A \sin(\omega t + \phi) = A \bigg(\sin(\omega t) \cos(\phi) + \cos(\omega t) \sin(\phi)\bigg)](https://img.qammunity.org/2023/formulas/mathematics/college/wzoaje5ge385e7eipfi3sd391ra552gahj.png)
and matching it up with the given expression, we see that
![\begin{cases} A \sin(\omega t) \cos(\phi) = 2 \sin(4\pi t) \\ A \cos(\omega t) \sin(\phi) = 5 \cos(4\pi t) \end{cases}](https://img.qammunity.org/2023/formulas/mathematics/college/etjic4ek4g2pdpzgzbqfth0c52lri3igez.png)
A natural choice for one of the symbols is
. Then
![\begin{cases} A \cos(\phi) = 2 \\ A \sin(\phi) = 5 \end{cases}](https://img.qammunity.org/2023/formulas/mathematics/college/bhyy8r25t38a2n4swrmxxn0albgkjfbyo5.png)
Use the Pythagorean identity to eliminate
.
![(A\cos(\phi))^2 + (A\sin(\phi))^2 = A^2 \cos^2(\phi) + A^2 \sin^2(\phi) = A^2 (\cos^2(\phi) + \sin^2(\phi)) = A^2](https://img.qammunity.org/2023/formulas/mathematics/college/lt5elxblz7kqs14i8n3p2rca26w2k5ecai.png)
so that
![A^2 = 2^2 + 5^2 = 29 \implies A = \pm√(29)](https://img.qammunity.org/2023/formulas/mathematics/college/6s4ihbnyvxomnuar8u3qmlbqh97pb0y5rs.png)
Use the definition of tangent to eliminate
.
![\tan(\phi) = (\sin(\phi))/(\cos(\phi)) = (A\sin(\phi))/(\cos(\phi))](https://img.qammunity.org/2023/formulas/mathematics/college/8led6oriindu1k1iozsbbit9no8fmu8jjj.png)
so that
![\tan(\phi) = \frac52 \implies \phi = \tan^(-1)\left(\frac52\right)](https://img.qammunity.org/2023/formulas/mathematics/college/57qsfycrcffu4slqz4c6eqkllve4uai81e.png)
We end up with
![y(t) = 2 \sin(4\pi t) + 5 \cos(4\pi t) = \boxed{\pm√(29) \sin\left(4\pi t + \tan^(-1)\left(\frac52\right)\right)}](https://img.qammunity.org/2023/formulas/mathematics/college/3z5cnxs7pjgmvjvz5o7lgdkppcj2g9uxua.png)
where
• amplitude:
![|A| = \boxed{√(29)}](https://img.qammunity.org/2023/formulas/mathematics/college/2yrkz201w9foiraout9wcgt7chizfw7ay1.png)
• angular frequency:
![\boxed{4\pi}](https://img.qammunity.org/2023/formulas/mathematics/college/mhmipo9985t079qa70g98bdmvlbh348mko.png)
• phase shift:
![4\pi t + \tan^(-1)\left(\frac 52\right) = 4\pi \left(t + \boxed{\frac1{4\pi} \tan^(-1)\left(\frac52\right)}\,\right)](https://img.qammunity.org/2023/formulas/mathematics/college/mstxfn3njjvxps6vtrhcuxmzx360opbgbo.png)